Factors associated with nursing and midwifery students’ satisfaction with the clinical learning environment: a cross-sectional study in Morocco - Khadija Guejdad; Laila Lahlou; Ali Ikrou; Redouane Abouqal; Jihane Belayachi (BMC Nursing)
Abstract Background Clinical practicum is a vital part of nursing education. A supportive clinical learning environment (CLE) is essential for students’ learning, professional integration, and well-being, as well as for ensuring high-quality patient care throughout their careers. This study aimed to evaluate nursing and midwifery students’ satisfaction with the CLE, and identify factors associated with their satisfaction in Morocco. Methods This cross-sectional study involved 1175 nursing and midwifery students from two Moroccan higher education institutes during the 2022 − 2023 academic year. Data was collected using the Arabic version of the Clinical Learning Environment, Supervision, and Nurse Teacher Scale (CLES + T). The mean scores of the overall CLES + T scale and its dimensions were calculated by averaging item ratings, with higher scores indicating greater satisfaction with the CLE. Student characteristics were analyzed using the student’s t-test or analysis of variance to assess satisfaction levels across groups. Linear regression was employed to identify factors linked to student satisfaction with the CLE. Results Students showed a moderate level of satisfaction with their clinical experiences, with a mean score of 3.21 out of 5. They expressed great satisfaction with the leadership style of the ward manager but reported decreased satisfaction with the supervisory relationship and the clinical role of the nurse teacher. The least satisfied were midwifery, last year students, those achieving their practicum in hospital wards, those with shorter placements, those who had unsuccessful supervision, and those without consistent supervisor meetings. Conclusions Significant enhancements are required in Morocco’s CLE. A shift from team supervision to individual supervision is recommended, accompanied by a robust preceptor training program to enhance clinical supervision. Moreover, nurse teachers should explore using new educational methods to substitute the lack of in-person interactions with students in clinical settings.